PKM Penulisan Karya Tulis Ilmiah - Faisal Faisal; Hartono Hartono; Arsad Bahri; A. Mushawwir Taiyeb; Yusnaeni Yusuf (JKM: Jurnal Kemitraan Masyarakat, 2023)
PKM Activities for Writing Scientific Papers at MTs Arifah, Gowa Regency is one of the service activities carried out by the State University Makassar of Biology Department Lecturer Team independently. From the results of observations and communication with teacher representatives, the majority of biology teachers at MTs Arifah Gowa spend most of their time completing ordinary teaching tasks. This means that teachers are trapped in work routines so that they do not carry out scientific writing activities to improve their abilities in writing. This is due to a number of reasons. One of these problems is a lack of knowledge regarding how to carry out scientific paper writing activities due to limited facilities and infrastructure. The aim of this training is to provide sufficient information and skills to partner groups on how to write scientific articles that are suitable for publication in accredited national scientific journals and how to publish them. The participants are expected to gain sufficient knowledge about how to write scientific articles that are suitable for publication in accredited national scientific journals. This training activity plans a training method consisting of three stages. First, participants are given material and information about techniques for writing and editing scientific articles for publication in accredited national scientific journals as well as strategies for publishing them in these journals. The second stage is the practice of writing scientific articles for publication in accredited national scientific journals. The third stage is a discussion and evaluation session.